Perceptions and attitudes above sustainable energy for some students of Secondary Education and activities proposal - García Fernández, Rubén; García Mozo, Alberto; Peña Martínez, Juan; Muñoz Muñoz, Alberto (M+A. Revista Electrónica de Medioambiente, 2017)
In this work, it has been studied the perceptions and attitudes about sustainable energy of two groups of students (2nd and 4th year of Secondary Education) of the Community of Madrid. The datacollection tool has consisted of an open questionnaire prepared based upon the literature. In addition, it has been performed an attractive and dynamic school activity based on the Winogradsky column as a previous work of the microbial fuel cells-taking into account that 2014 was declared the year of Biotechnology in Spain. This proposal may be considered a reference point for teachers who want to reinforce and extend content of Physics, Chemistry and Biology in the framework of a responsible and committed Environmental Education in Secondary Education. Transversely but not least, we have tried with this proposal to increase the interest in the experimental sciences and encourage new scientific vocations among the students.
Keywords: Sustainable development; sustainable energy; environmental education and Secondary Education.